Indoor Thermal Comfort in Tropical Urban Houses in Indonesia: The Effect of Outdoor Temperature and Windows - Nur Azizah, Jihan; Joana Febrita; Yudi Chadirin (Jurnal Teknik Sipil dan Lingkungan, 2025)
Indoor thermal comfort in tropical urban houses is important to manage because it determines the quality of life for the inhabitants. However, it is prone to sudden changes of temperature, especially in a developing country, such as Indonesia, where indoor air circulation is mainly supported by windows. This research aims to evaluate the indoor thermal comfort in Indonesian urban houses, and to analyse the correlation of outdoor temperature and the number of windows on the indoor temperature. This study took place in the Greater Bogor Area with a total of five houses. Outdoor and indoor temperatures were monitored in four areas for each home, which are the living room, bedroom, toilet, and terrace. The dry and wet temperatures were analysed to determine the indoor thermal comfort status based on ASHRAE (The American Society of Heating, Refrigerating, and Air Conditioning Engineers)-55. The correlation between outdoor temperature and the number of windows on indoor thermal comfort was analysed using multiple linear regression. Three of the five houses had areas that met the standard for thermal comfort. The areas were mainly the terrace and the bedroom. The average (standard deviation) of outdoor dry and wet temperatures was 27.79 oC (1.03 oC), and 25.59 oC (1.56 oC), respectively. While for the indoors, the average for dry and wet temperatures were 27.96 oC (1.87 oC), and 25.39 oC (2.31 oC). Outdoor temperature and number of windows showed insignificant correlation with indoor temperature (R2: 0.1448; adj R2: 0.08145; p>0.121), opposing the previous studies on the effect of outdoor temperature and number of windows on indoor temperature. Apart from this finding, the effect of windows/ventilation's presence on indoor thermal comfort cannot be undermined. As ventilation serves as a part of human adaptation to heat, it is becoming more important amidst the increased extreme heat caused by climate change.